Penilaian Diri dan Penilaian Reflektif - Bismar Sibuea; Suriyadi Suriyadi; Fakhruddin Azmi; Nurika Khalila Daulay (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Education Management as a scientific discipline is of course also part of a transdisciplinary study which in solving problems in the world of education can certainly apply the transdisciplinary principles themselves. Along with the times, the world of education has also transformed into a science that involves many things, education is no longer merely a scientific discipline that reviews pedagogic science, but has involved various disciplines. Even if seen from the rise of non-governmental educational institutions, they have actually approached the business world, which is purely outside of the pedagogic discipline itself. This research is a research that uses the method of literature study or literature review. Literature study research is a process or activity of collecting data from various literature such as books and journals to compare the results of one study with another. The method of self-assessment and reflective assessment in the world of education is very possible to be carried out by teachers and lecturers in the learning process, these methods even have unique advantages from other learning methods. This method motivates students to reflect on themselves, activities, abilities possessed by students themselves and then reflect on themselves by assessing themselves and their own abilities to make improvements to themselves with the system, or the method they choose according to their abilities own.